DEVELOPING TEACHING MATERIALS FOR LISTENING FOR GENERAL PURPOSES SUBJECT - Hustarna Hustarna; Masbirorotni Masbirorotni (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2023)
ABSTRACTListening for General Purposes is one of the compulsory subjects in the English study program at one of the public universities in Indonesia. In the teaching and learning process, the lecturers often find difficulties in finding appropriate materials that fit the curriculum and students' interests. This research aimed to develop teaching materials for the Listening for general Purposes subject. The developed teaching materials were in the form of a textbook with attractive videos. The topics were selected based on the characteristics of the students and the result of the needs analysis questionnaire. This research employed a Research and Development design based on the theory developed by Borg and Gall (1983). The result of the research is a listening textbook with attractive videos. With such a textbook, it is hoped that the lecturers teaching Listening for General Purposes will no longer find it difficult to teach this subject. Besides, videos are hoped to encourage students to be more active in the teaching and learning process. The developed product is expected to also be used by other lecturers teaching listening in other universities when the result of the implementation of the product yields positive results in further research. ABSTRAKListening for General Purposes adalah salah satu mata kuliah wajib yang dicantumkan dalam kurikulum program studi Bahasa Inggris di salah satu universitas negeri di Indonesia. Dalam proses pembelajaran, dosen sering menemukan kesulitan dalam mendapatkan bahan ajar yang menarik dan sesuai dengan kurikulum. Penelitian ini bertujuan untuk mengembangkan bahan ajar untuk mata kuliah Listening for General Purposes. Bahan ajar yang dikembangkan berupa buku teks yang dilengkapi dengan video-video menarik. Pilihan topik pembelajaran disesuaikan dengan karakteristik mahasiswa dan berdasarkan hasil angket analisis kebutuhan yang diberikan ke partisipan mahasiswa. Penelitian ini menggunakan rancangan penelitian Riset dan Pengembangan berdasarkan teori Borg dan Gall (1983). Hasil dari penelitian ini adalah buku listening yang dilengkapi dengan video. Dengan adanya buku teks tersebut diharapkan dosen yang mengajar Listening for General Purposes tidak lagi menemui kesulitan dalam menentukan bahan ajar yang akan digunakan. Di samping itu, video-video yang digunakan diharapkan bisa mendorong mahasiswa untuk lebih aktif dalam proses pembelajaran listening tersebut.How to Cite: Hustarna, Masbirorotni. (2023). Developing Teaching Materials for Listening for General Purposes Subject. IJEE (Indonesian Journal of English Education), 10(2), 389-408. doi:10.15408/ijee.v10i2.32202.